Ionizing Irradiation Not Only Inactivates Clonogenic Potential in Primary Normal Human Diploid Lens Epithelial Cells but Also Stimulates Cell Proliferation in a Subset of This Population - Fujimichi, Yuki (Public Library of Science, 2014)
Over the past century, ionizing radiation has been known to induce cataracts in the crystalline lens of the eye, but its mechanistic underpinnings remain incompletely understood. This study is the first to report the clonogenic survival of irradiated primary normal human lens epithelial cells and stimulation of its proliferation. Here we used two primary normal human cell strains: HLEC1 lens epithelial cells and WI-38 lung fibroblasts. Both strains were diploid, and a replicative lifespan was shorter in HLEC1 cells. The colony formation assay demonstrated that the clonogenic survival of both strains decreases similarly with increasing doses of X-rays. A difference in the survival between two strains was actually insignificant, although HLEC1 cells had the lower plating efficiency. This indicates that the same dose inactivates the same fraction of clonogenic cells in both strains. Intriguingly, irradiation enlarged the size of clonogenic colonies arising from HLEC1 cells in marked contrast to those from WI-38 cells. Such enhanced proliferation of clonogenic HLEC1 cells was significant at ≥2 Gy, and manifested as increments of ≤2.6 population doublings besides sham-irradiated controls. These results suggest that irradiation of HLEC1 cells not only inactivates clonogenic potential but also stimulates proliferation of surviving uniactivated clonogenic cells. Given that the lens is a closed system, the stimulated proliferation of lens epithelial cells may not be a homeostatic mechanism to compensate for their cell loss, but rather should be regarded as abnormal. This is because these findings are consistent with the early in vivo evidence documenting that irradiation induces excessive proliferation of rabbit lens epithelial cells and that suppression of lens epithelial cell divisions inhibits radiation cataractogenesis in frogs and rats. Thus, our in vitro model will be useful to evaluate the excessive proliferation of primary normal human lens epithelial cells that may underlie radiation cataractogenesis, warranting further investigations.